Mood state moderates the role of serotonin in cognitive biases. - Robinson, O; Cools, R; Crockett, M; Sahakian, B (2010)
Reduction of the monoamine serotonin (5-HT) via the dietary manipulation of tryptophan (acute tryptophan depletion; ATD) has been shown to induce negative cognitive biases similar to those found in depression in healthy individuals. However, evidence also indicates that there can be positive effects of ATD on both mood and reinforcement processing. Here, we present two separate studies, with remarkably similar findings, which may help explain these discrepancies. In both experiments, we assessed cognitive biases following experimentally induced mood states under both a balanced amino acid drink (BAL) and ATD. A significant interaction between treatment, mood state and cognitive bias was observed in both experiments. In the first experiment, subjects undergoing positive mood induction demonstrated a positive cognitive bias on BAL, which was abolished by ATD. The same effect was observed in subjects undergoing neutral mood induction in the second experiment. These effects replicate findings in healthy individuals undergoing ATD. Subjects undergoing negative mood induction, by contrast, demonstrated the opposite pattern of results; in both experiments, they showed no bias under BAL but induction of a positive cognitive bias by ATD. These results mimic previous findings in currently depressed patients undergoing ATD. We therefore suggest that mood state moderates the effect of ATD on cognitive biases. This, in turn, has important implications for the understanding of the role of 5-HT in psychiatric disorders.